HUBUNGAN KONDISI SANITASI DAN PERSONAL HIGIENE PEKERJA DENGAN JUMLAH ANGKA KUMAN PADA IKAN ASAP DI BANDARHARJO KOTA SEMARANG - Fatikha Firdausi; Mursid Rahardjo; Yusniar Hanani Darundiati (Jurnal Kesehatan Masyarakat (Undip), 2017)
Smoked fish products may endanger consumers due to bacterial contamination. Microbial contamination of smoked fish is due to the fact that during the process of smoking, the sanitary and personal hygine levels of hygine of workers are poor. The purpose of this study is to analyze the relationship between sanitary conditions and personal hygine of workers with the number of germs in smoked fish. The type of this research were analytic survey research using cross sectional approach. The population and samples in this research were 21 centers of cottage industry with total sampling method. The research was conducted by laboratory examination, observation by using check list sheet, interview using questionaire and then analyzed univariat, bivariate using chi square test and multivariate with logistic regression statistic test. The results showed that there were six variables that were found to be related to the contamination of number of germs in smoked fish, namely the quality of clean water (p=0,0001), garbage condition (p=0,017), sanitary condition of equipment (p=0,0001), presence of vector and pest (p=0,004), hand washing practice (p=0,001), and nail hygiene (p=0,003). The most dominant variable affecting the number of germs in smoked fish is nail hygiene (p=0,027) with the biggest risk value obtained is 23,350.